(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The effect of dialkylsulfoxides (DASO) on the thermal denaturation of serum albumins human and bovine in the temperature range 20–90oC has been investigated by the UV/vis absorption spectroscopy method. It has been shown that in the homologous series of DASO hydrophobic interactions with proteins become more effective. However, with the elongation of hydrocarbon chain, starting from dipropylsulfoxide, in consequence of breaking the diffusion of sulfoxide molecules, denaturation of proteins is observed at higher temperatures.